Coal accumulation control on gas and coalbed methane exploration potential in southern Ordos Basin: A case study of Carboniferous Taiyuan Formation in Xunyi exploration area - WANG Liangjun, WANG Yong, ZHANG Xinwen, JIN Yunyun, ZHU Yan, ZHANG Gaoyuan, LI Hui, LI Wangju (Youqicang pingjia yu kaifa)
Based on the analysis of the coal-forming environment of the Carboniferous Taiyuan Formation in Xunyi exploration area, southern Ordos Basin, and combined with paleogeomorphological analysis and sedimentary facies research, the coal accumulation characteristics of Taiyuan Formation were identified. By using experimental analysis methods such as industrial analysis, scanning electron microscopy, and isothermal adsorption, along with well-logging modeling evaluation, the characteristics of coal petrology and coal quality, reservoir physical properties, and gas content were investigated. The key controlling factors for deep coalbed methane accumulation and reservoir formation characteristics were analyzed and summarized, identifying favorable zones for further exploration. Integrated with coalbed methane exploration practice, it was confirmed that deep coalbed methane had promising exploration potential. Research showed that: (1) the development of coal seams in the Carboniferous Taiyuan Formation in the Xunyi exploration area was influenced by two coal-forming environments: tidal flat peat bogs and lagoon peat bogs. Due to the influence of coal-forming environments and sedimentary paleogeomorphology, the coal seam distribution exhibited a “thin in the west and thick in the east” coal accumulation pattern. (2) The coal lithotypes were primarily bright coal and semi-bright coal, with the coal body structures mainly characterized by primary and fractured types. The types of reservoir space included plant cell lumen pores, intercrystalline pores of pyrite and clay minerals, and cleat fractures. (3) The gas content of coal seams ranged from 15.8 to 25.6 m³/t, indicating moderate to good gas-bearing properties. The enrichment of coalbed methane was controlled by factors such as the coal-forming environment, tectonic evolution, and preservation conditions. (4) The northwest slope area was characterized by underdeveloped faults, normal formation pressure, weak formation hydrodynamics, and large coal seam burial depth, making it a favorable zone for deep normal-pressure coalbed methane exploration. The southeast fault slope area had relatively developed faults, low formation pressure, strong formation hydrodynamics, and moderate coal seam burial depth, making it a favorable zone for medium-to-deep low-pressure coalbed methane exploration. The PZ1 well, located in the southeast fault slope area, produced a low gas flow during coal seam fracturing tests, demonstrating the promising exploration potential of deep coalbed methane in the structurally complex margin of the Ordos Basin.